Visitor's Characteristic and Motivation at Museum Prasasti as Dark Tourism Site in Jakarta - Risang Dahana Giri (Gadjah Mada Journal of Tourism Studies, 2019)
Tourists are pushed to travel to different destinations, either pleasant or macabre destinations, for various motives. Tourist motivation which determines one’s behaviour can be used to understand the tourists’ needs, destination, and choice of activities. This research aimed to investigate local tourists’ characteristics and motivation for visiting Museum Prasasti, which formerly served as a Dutch cemetery. It was conducted due to the limited number of researches on tourists’ visitation to cemetery sites in Indonesia. The research was conducted at Museum Prasasti, Jakarta. The data collection gained from the paper-based questionnaires using the Likert scale. This quantitative method was used to measure tourists’ tendency during their stay at Museum Prasasti. The measurement of motivation was divided into four major motivations: engaging entertainment, dark experience, unique learning experience, and casual interest. By collecting the data from101 responses, this research shows that local tourists at Museum Prasasti are mostly female, under the age of 30, students, and come from lower-middle-class society. The unique learning experience is the most favourable motivation that drives local tourists to visit Museum Prasasti. They visit the museum for educational purposes (to increase their knowledge, understand well-known places regarding their historical heritage, and learn their history). The dark experience motivation least likely motivates them (to see well-known locations for their paranormal activity, experience paranormal activity firsthand, and witness the aftermath of deaths).